Compendium of quantum physics : concepts, experiments, history, and philosophy - Greenberger, Daniel; Hentschel, Klaus; Weinert, Friedel (Berlin : Springer-Verlag, 2009)
"With contributions by many of today's leading quantum physicists, philosophers and historians, including three Nobel laureates, this comprehensive A to Z of quantum physics provides a lucid understanding of the key concepts of quantum theory and experiment. It covers technical and interpretational aspects alike, and includes both traditional topics and newer areas such as quantum information and its relatives. The central concepts that have shaped contemporary understanding of the quantum world are clearly defined, with illustrations where helpful, and discussed at a level suitable for undergraduate and graduate students of physics, history of science, and philosophy of physics. All articles share three main aims: (1) to provide a clear definition and understanding of the term concerned; (2) where possible, to trace the historical origins of the concept; and (3) to provide a small but optimal selection of references to the most relevant literature, including pertinent historical studies. Also discussed are the often contentious philosophical implications derived from quantum theory and its associated experimental findings." "This compendium will be an indispensable resource for all those seeking concise up-to-date information about the many facets of quantum physics."--Jacket.
Includes bibliographical references.
Keywords: Quantum theory